Digital workplace and SMEs performance: How the Mediating role of digital leadership capability? - Suyudi , Suyudi; Setyawati, Endang; Widiastuti, Rosalina Yani; Hermanto , Diwahana Mutiara Candrasari; Lianawati, Yosita; Wibowo , Adhi (International Journal of Social and Management Studies, 2023)
AbstractThe aim of this research is to analyze the relationship between digital workplace variables and SMEs performance, analyze the relationship between digital leadership variables and SMEs performance, analyze the relationship between digital leadership capability variables and digital workplaces, analyze the relationship between digital workplace and leadership digital capability variables, the mediating role of digital leadership capability variables in the relationship. digital workplace and SMEs performance. This research method is quantitative through an online survey, research data was obtained by distributing online questionnaires to 639 SMEs owners in Indonesia who were selected using a simple random sampling method. Data analysis used structural equation modeling (SEM) partial least squares (PLS) with the SmartPLS 3.0 software tool. The questionnaire contains statement items and is designed using a 9 scale Likert scale. The data analysis stages are validity testing, reliability testing and direct and indirect hypothesis testing or mediation effect testing. The independent variable in this research is digital work place, the dependent variable is SMEs performance and the mediating variable is the digital leadership capability variable. The research results show that the digital leadership variable has a positive and significant relationship to SMEs performance, the digital workplace variable has a positive and significant relationship to digital capability, the digital leadership capability variable has a role as a full mediator in the relationship between digital workplace leadership and SMEs performance. The novelty of this research is the creation of a model of the relationship between digital workplace variables, SMEs performance and the mediating role of digital leadership capability variables.